2014
DOI: 10.1007/s00277-014-2028-x
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening hemorrhagic pneumonia caused by Stenotrophomonas maltophilia in the treatment of hematologic diseases

Abstract: Since the late 1990s, Stenotrophomonas maltophilia (S. maltophilia) has become one of the most common nonfermenting Gram-negative bacilli that cause opportunistic infection. Patients with hematologic diseases are the most risky candidate for S. maltophilia pneumonia or sepsis because of chemotherapy-induced neutropenia or immunodeficiency. Frequent exposure to broad-spectrum antibiotics and prolonged insertion of central venous catheter further enhance the risk of S. maltophilia infection. One of the most seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 65 publications
1
47
0
Order By: Relevance
“…Cases of haemorrhagic pneumonia associated with SM have been reported only in patients with haematological disorders. Mori et al [3] reviewed all cases in the literature that reported patients with haemorrhagic pneumonia caused by SM. They emphasised that SM leads to fulminant and fatal haemorrhagic pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of haemorrhagic pneumonia associated with SM have been reported only in patients with haematological disorders. Mori et al [3] reviewed all cases in the literature that reported patients with haemorrhagic pneumonia caused by SM. They emphasised that SM leads to fulminant and fatal haemorrhagic pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation might be severe with diffuse alveolar hemorrhage and respiratory failure. 50 Although many neutropenic patients do not produce sputum, a microbiologic analysis of sputum (Gram staining and culture) might help to establish the etiology of PI.…”
Section: Imagesmentioning
confidence: 99%
“…, Serratia marcescens , Acinetobacter baumannii -complex and Proteus spp. (15, 41, 43, 44, 4952) Unfortunately, the rise in Gram-negative neutropenic respiratory infections has also yielded a corresponding increase in extended spectrum beta-lactamase producing Enterobacteriaceae. Mortality rates associated with drug resistant P. aeruginosa and MRSA are disproportionately higher than those caused by other nosocomial bacterial pathogens.…”
Section: Microbiology and The Spectrum Of Pathogensmentioning
confidence: 99%